Logical Intuitive Aspect of the Story in the Quran: Sayyid Quthb’s Perspective - Asyhad Abdillah Rosyid (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The content explains the intuitive and logical aspects of the stories in the Koran. Intuition is a source of knowledge based on belief and experience. This dimension is found in the story of the Qur'an in various forms, initially in nature and unseen. It cannot be measured, but ultimately, it becomes logical because it is based on the laws that apply in society and can be validated through modern scientific approaches. It is what is called logical Intuition. This intuitive, logical aspect is found in Qur'an stories, which are attached to the principal or supporting characters and the story's plot. It is not revealed in the storyline, characterization, and message. Different from what was crystallized by Sayyid Quthb. He is an interpreter and writer who is clever at using persuasive narratives to arouse mental awareness and is straightforward so that it can be accepted by reason because it is by the realities of life and the laws that apply and develop in society. Perspective This is used as an approach to show the intuitive and logical aspects of the stories in the Qur'an.